Evaluation of occupational exposure in healthcare workers via a trio-strategy of pre-KAP survey, educational intervention, and post-KAP survey - Prakash, Himanshi; Garg, Jaya; Sen, Manodeep; Gupta, Nikhil; Agarwal, Jyotsna; Kapoor, Kamini; Pathak, Anurag (International Journal of Infection Control, 2025)
Background: Occupational exposures in form of sharps injury, splashes are common among healthcare workers (HCWs). There is a need to identify associated risks and provide focused training sessions accordingly. Knowledge, Attitude and Practices (KAP) survey has emerged as an effective tool to measure impact of trainings. In this study we are evaluating the impact of occupational safety training among health care workers via pre and post KAP surveys. Aims: To estimate the prevalence of self-reported occupational exposures and evaluate the risk factors associated with it. To assess the impact of single educational session on healthcare workers. Methods: All exposures based on self-reporting were recorded and evaluated. Impact of education on HCWs was evaluated via a Trio strategy of pre-KAP, followed by educational session and post- KAP assessment surveys. Findings: The prevalence of self-reported occupational exposure was found to be 3.88%, most commonly in nurses (27%) and primarily during blood sample collection (19%). Detailed data was compiled for risk factor analysis. Significant improvements (p<0.001), in knowledge, attitude and practices were recorded with 33.6%, 19.1% and 26.7% respectively, after the educational session. Conclusion: Focused and multiple educational sessions are required to increase reporting of exposure events and consolidation of knowledge, positive attitude and good practices in HCWs.